Co-ingestion of caffeine and carbohydrate after meal does not improve performance at high-intensity intermittent sprints with short recovery times - Lee, C.-L.; Cheng, C.-F.; Lee, C.-J.; Kuo, Y.-H.; Chang, W.-D. (European Journal of Applied Physiology, 2014)
Abstract: Purpose: To determine the effects of co-ingesting caffeine (CAF) and carbohydrate (CHO) on high-intensity intermittent sprints (HIS) performance and physiological responses. Methods: Twelve active males underwent 4 interventions at least 7 days apart in a randomized, double-blind, placebo-controlled, balanced trial. A meal contained 65 % CHO was provided 2 h before the HIS test. Participants ingested the placebo (PLA) or CAF (6 mg kg-1 BW) 1 h before taking an HIS test, and ingested a PLA or CHO solution (0.8 g kg-1 BW) before undergoing the testing protocol. The HIS protocol comprised ten sets of 5 × 4-s sprints on a cycle ergometer with a 2-min recovery between each set. Results: There was no significant difference between peak power output and mean power output between trials (p > 0.05). Compared with PLA, CAF + CHO resulted in a 5.2 % reduction in total work, corresponding to a 24.7-25.7 % increase in fatigue at the end stage of the HIS. The administration of CAF + CHO supplementation also resulted in an 11.1 % increase in blood lactate, and elevated blood glucose concentrations throughout HIS testing compared with PLA (p < 0.05). Cortisol concentrations also increased with CAF + CHO intake compared with PLA; however, there was no significant effect of CAF + CHO supplementation on testosterone concentrations. Conclusion: Co-ingestion of CAF and CHO did not improve high-intensity sprint cycling performance or reduce fatigue in active males. Moreover, combined CAF and CHO supplementation might facilitate catabolism during prolonged high-intensity intermittent exercise.